Treatment process for improving surface performance of raw material of spring tube of pressure gauge
By adjusting the elemental composition and process processing of magnesium-aluminum alloy, the problems of poor corrosion resistance and low strength in pressure gauge applications have been solved, and the corrosion resistance and strength of magnesium-aluminum alloys have been significantly improved. It is suitable for many Working conditions.
Patent Information
- Application Number
- CN202411337810.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-02-11
AI Technical Summary
Traditional magnesium-aluminum alloys have problems of poor corrosion resistance and low strength in pressure gauge applications, which affect their service life and accuracy in different environments.
By adjusting the elemental composition and content of magnesium-aluminum alloy, melting it in an argon environment using a low temperature first and then high temperature heating method, adding a variety of intermediate alloys and performing solid solution strengthening and aging treatment, we can produce an optimized corrosion resistance and strength with optimized corrosion resistance and strength Magnesium aluminum alloy.
It significantly improves the corrosion resistance and strength of magnesium-aluminum alloy, enhances its adaptability and processability in different fields and working conditions, and ensures the quality of comprehensive use.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of production and processing of pressure gauge spring tubes, and in particular relates to a treatment process for improving the surface performance of raw materials of pressure gauge spring tubes. Background Art
[0002] The working environment of the pressure gauge mainly includes temperature, humidity, installation method and environmental pollution. These factors will directly affect the accuracy and service life of the pressure gauge. Magnesium-aluminum alloy has the advantages of low density, high specific strength and specific stiffness, good thermal and electrical conductivity, damping and vibration reduction, electromagnetic shielding, easy processing and molding, and easy recycling of waste. It is a commonly used raw material for pressure gauge spring tubes.
[0003] Although conventional magnesium-aluminum alloys are easy to form, they have the disadvantages of poor corrosion resistance and low strength. Research is ongoing to appropriately change the composition of magnesium-aluminum alloys in order to improve the corrosion resistance and strength of magnesium-aluminum alloys. Summary of the invention
[0004] The purpose of the invention is to provide a processing technology for improving the surface performance of a pressure gauge spring tube raw material.
[0005] The above technical objectives of the present invention are achieved through the following technical solutions: A processing technology for improving the surface performance of a pressure gauge spring tube raw material comprises the following steps: (1) First, pure magnesium, aluminum ingots, and zinc ingots are mixed together, and then put into a furnace for melting. The melting process is carried out by heating at low temperature first and then at high temperature; (2) Adding Mg-Mn master alloy, Mg-Li master alloy, Al-Zr master alloy, Mg-Mo master alloy, Mg-Ti master alloy, Mg-Si master alloy, Mg-Ca master alloy, Mg-Ag master alloy, Al-Mg-Sb master alloy, Al-Mg-Se master alloy, Al-Cr master alloy, Mg-La master alloy and Mg-Y master alloy into the melting furnace of step (1) in sequence; and melting them together to obtain a molten material; (3) transferring the molten material obtained in step (2) into a refining furnace, leaving it to stand for 40 to 50 minutes and then casting it into an ingot, and then removing the cold shut and oxide layer on the surface of the ingot to obtain a primary magnesium-aluminum alloy ingot; (4) The primary magnesium-aluminum alloy ingot obtained in step (3) is subjected to solid solution strengthening and aging treatment to obtain a finished magnesium-aluminum alloy.
[0006] Furthermore, during the melting in step (1), the environment in the furnace is controlled to be an argon environment.
[0007] Furthermore, the heating method of first low temperature and then high temperature in step (1) is specifically to first heat the furnace to 650-700°C, keep the temperature for 25-30 minutes, and then heat the furnace to 800-840°C, and keep the temperature for 20-25 minutes.
[0008] Furthermore, the mass percentage contents of the components in the melt described in step (2) are as follows: Al: 6-9%, Zn: 2-3.5%, Mn: 1.5-2.5%, Li: 0.4-0.8%, Zr: 0.2-0.6%, Mo: 0.1-0.4%, Ti: 0.5-0.9%, Si: 0.2-0.5%, Ca: 0.3-0.6%, Ag: 0.1-0.3%, Sb: 0.18-0.30%, Se: 0.2-0.35%, Cr: 0.05-0.12%, La: 0.2-0.4%, Y: 0.3-0.5%, and the balance is Mg.
[0009] Preferably, the mass percentage content of each component in the molten material is as follows: Al: 8%, Zn: 3%, Mn: 2%, Li: 0.6%, Zr: 0.4%, Mo: 0.3%, Ti: 0.8%, Si: 0.4%, Ca: 0.5%, Ag: 0.2%, Sb: 0.25%, Se: 0.3%, Cr: 0.08%, La: 0.3%, Y: 0.4%, and the balance is Mg.
[0010] Furthermore, during the static treatment in step (3), the refining furnace is controlled to be in an argon gas environment.
[0011] Furthermore, the temperature in the refining furnace in step (3) is controlled to be 660-720°C.
[0012] Compared with the prior art, the present invention has the following advantages: The present invention rationally adjusts the element composition and content in the magnesium-aluminum alloy, optimizes and adjusts the potential difference between the matrix magnesium and other alloying elements on the basis of ensuring the overall strength and other mechanical properties of the magnesium-aluminum alloy, realizes good enhancement and adjustment of the overall corrosion resistance, improves the machinability of the magnesium-aluminum alloy in different fields and working conditions, and ensures its comprehensive use quality. The method of the present invention has a simple process, can ensure the stability of the characteristics of the magnesium-aluminum alloy, has great promotion and application value, strong market competitiveness, and high production efficiency. DETAILED DESCRIPTION Example 1
[0013] A processing technology for improving the surface performance of a pressure gauge spring tube raw material comprises the following steps: (1) First, pure magnesium, aluminum ingots, and zinc ingots are mixed together, and then put into a furnace for melting. The environment in the furnace is controlled to be an argon environment, and a heating method of first low temperature and then high temperature is adopted during melting; specifically, the furnace is first heated to 650°C, and the temperature is kept for 25 minutes, and then the furnace is heated to 800°C and the temperature is kept for 20 minutes; (2) Adding Mg-Mn master alloy, Mg-Li master alloy, Al-Zr master alloy, Mg-Mo master alloy, Mg-Ti master alloy, Mg-Si master alloy, Mg-Ca master alloy, Mg-Ag master alloy, Al-Mg-Sb master alloy, Al-Mg-Se master alloy, Al-Cr master alloy, Mg-La master alloy and Mg-Y master alloy into the melting furnace of step (1) in sequence; and melting them together to obtain a molten material; (3) transferring the molten material obtained in step (2) into a refining furnace, leaving it to stand for 40 minutes and then casting it into an ingot, then removing the cold shut and oxide layer on the surface of the ingot to obtain a primary magnesium-aluminum alloy ingot; during the standing treatment, the refining furnace is controlled to be an argon environment; the temperature in the refining furnace is controlled to be 660°C; (4) The primary magnesium-aluminum alloy ingot obtained in step (3) is subjected to solid solution strengthening and aging treatment to obtain a finished magnesium-aluminum alloy.
[0014] The mass percentage content of each component in the molten material described in step (2) is as follows: Al: 6%, Zn: 2%, Mn: 1.5%, Li: 0.4%, Zr: 0.2%, Mo: 0.1%, Ti: 0.5%, Si: 0.2%, Ca: 0.3%, Ag: 0.1%, Sb: 0.18%, Se: 0.2%, Cr: 0.05%, La: 0.2%, Y: 0.3%, and the balance is Mg. Example 2
[0015] A processing technology for improving the surface performance of a pressure gauge spring tube raw material comprises the following steps: (1) First, pure magnesium, aluminum ingots, and zinc ingots are mixed together, and then put into a furnace for melting. The environment in the furnace is controlled to be an argon environment, and a heating method of first low temperature and then high temperature is adopted during melting; specifically, the furnace is first heated to 650°C, and the temperature is kept for 25 minutes, and then the furnace is heated to 800°C and the temperature is kept for 20 minutes; (2) Adding Mg-Mn master alloy, Mg-Li master alloy, Al-Zr master alloy, Mg-Mo master alloy, Mg-Ti master alloy, Mg-Si master alloy, Mg-Ca master alloy, Mg-Ag master alloy, Al-Mg-Sb master alloy, Al-Mg-Se master alloy, Al-Cr master alloy, Mg-La master alloy and Mg-Y master alloy into the melting furnace of step (1) in sequence; and melting them together to obtain a molten material; (3) transferring the molten material obtained in step (2) into a refining furnace, leaving it to stand for 40 minutes and then casting it into an ingot, then removing the cold shut and oxide layer on the surface of the ingot to obtain a primary magnesium-aluminum alloy ingot; during the standing treatment, the refining furnace is controlled to be an argon environment; the temperature in the refining furnace is controlled to be 660°C; (4) The primary magnesium-aluminum alloy ingot obtained in step (3) is subjected to solid solution strengthening and aging treatment to obtain a finished magnesium-aluminum alloy.
[0016] The mass percentage content of each component in the molten material described in step (2) is as follows: Al: 8%, Zn: 3%, Mn: 2%, Li: 0.6%, Zr: 0.4%, Mo: 0.3%, Ti: 0.8%, Si: 0.4%, Ca: 0.5%, Ag: 0.2%, Sb: 0.25%, Se: 0.3%, Cr: 0.08%, La: 0.3%, Y: 0.4%, and the balance is Mg. Example 3
[0017] A processing technology for improving the surface performance of a pressure gauge spring tube raw material comprises the following steps: (1) First, pure magnesium, aluminum ingots, and zinc ingots are mixed together, and then put into a furnace for melting. The environment in the furnace is controlled to be an argon environment. During melting, a heating method of first low temperature and then high temperature is adopted; specifically, the furnace is first heated to 680°C, and the temperature is kept for 27 minutes, and then the furnace is heated to 820°C and the temperature is kept for 23 minutes; (2) Adding Mg-Mn master alloy, Mg-Li master alloy, Al-Zr master alloy, Mg-Mo master alloy, Mg-Ti master alloy, Mg-Si master alloy, Mg-Ca master alloy, Mg-Ag master alloy, Al-Mg-Sb master alloy, Al-Mg-Se master alloy, Al-Cr master alloy, Mg-La master alloy and Mg-Y master alloy into the melting furnace of step (1) in sequence; and melting them together to obtain a molten material; (3) transferring the molten material obtained in step (2) into a refining furnace, leaving it to stand for 45 minutes and then casting it into an ingot, then removing the cold shut and oxide layer on the surface of the ingot to obtain a primary magnesium-aluminum alloy ingot; during the standing treatment, the refining furnace is controlled to be an argon environment; the temperature in the refining furnace is controlled to be 680°C; (4) The primary magnesium-aluminum alloy ingot obtained in step (3) is subjected to solid solution strengthening and aging treatment to obtain a finished magnesium-aluminum alloy.
[0018] The mass percentage content of each component in the molten material described in step (2) is as follows: Al: 8%, Zn: 3%, Mn: 2%, Li: 0.6%, Zr: 0.4%, Mo: 0.3%, Ti: 0.8%, Si: 0.4%, Ca: 0.5%, Ag: 0.2%, Sb: 0.25%, Se: 0.3%, Cr: 0.08%, La: 0.3%, Y: 0.4%, and the balance is Mg. Example 4
[0019] A processing technology for improving the surface performance of a pressure gauge spring tube raw material comprises the following steps: (1) First, pure magnesium, aluminum ingots, and zinc ingots are mixed together, and then put into a furnace for melting. The environment in the furnace is controlled to be an argon environment, and a heating method of first low temperature and then high temperature is adopted during melting; specifically, the furnace is first heated to 700°C, and the temperature is kept for 30 minutes, and then the furnace is heated to 840°C and the temperature is kept for 25 minutes; (2) Adding Mg-Mn master alloy, Mg-Li master alloy, Al-Zr master alloy, Mg-Mo master alloy, Mg-Ti master alloy, Mg-Si master alloy, Mg-Ca master alloy, Mg-Ag master alloy, Al-Mg-Sb master alloy, Al-Mg-Se master alloy, Al-Cr master alloy, Mg-La master alloy and Mg-Y master alloy into the melting furnace of step (1) in sequence; and melting them together to obtain a molten material; (3) transferring the molten material obtained in step (2) into a refining furnace, leaving it to stand for 50 minutes and then casting it into an ingot, then removing the cold shut and oxide layer on the surface of the ingot to obtain a primary magnesium-aluminum alloy ingot; during the standing treatment, the refining furnace is controlled to be an argon environment; the temperature in the refining furnace is controlled to be 720°C; (4) The primary magnesium-aluminum alloy ingot obtained in step (3) is subjected to solid solution strengthening and aging treatment to obtain a finished magnesium-aluminum alloy.
[0020] The mass percentage content of each component in the molten material described in step (2) is as follows: Al: 9%, Zn: 3.5%, Mn: 2.5%, Li: 0.8%, Zr: 0.6%, Mo: 0.4%, Ti: 0.9%, Si: 0.5%, Ca: 0.6%, Ag: 0.3%, Sb: 0.30%, Se: 0.35%, Cr: 0.12%, La: 0.4%, Y: 0.5%, and the balance is Mg. Example 5
[0021] A processing technology for improving the surface performance of a pressure gauge spring tube raw material comprises the following steps: (1) First, pure magnesium, aluminum ingots, and zinc ingots are mixed together, and then put into a furnace for melting. The environment in the furnace is controlled to be an argon environment, and a heating method of first low temperature and then high temperature is adopted during melting; specifically, the furnace is first heated to 700°C, and the temperature is kept for 30 minutes, and then the furnace is heated to 840°C and the temperature is kept for 25 minutes; (2) Adding Mg-Mn master alloy, Mg-Li master alloy, Al-Zr master alloy, Mg-Mo master alloy, Mg-Ti master alloy, Mg-Si master alloy, Mg-Ca master alloy, Mg-Ag master alloy, Al-Mg-Sb master alloy, Al-Mg-Se master alloy, Al-Cr master alloy, Mg-La master alloy and Mg-Y master alloy into the melting furnace of step (1) in sequence; and melting them together to obtain a molten material; (3) transferring the molten material obtained in step (2) into a refining furnace, leaving it to stand for 50 minutes and then casting it into an ingot, then removing the cold shut and oxide layer on the surface of the ingot to obtain a primary magnesium-aluminum alloy ingot; during the standing treatment, the refining furnace is controlled to be an argon environment; the temperature in the refining furnace is controlled to be 720°C; (4) The primary magnesium-aluminum alloy ingot obtained in step (3) is subjected to solid solution strengthening and aging treatment to obtain a finished magnesium-aluminum alloy.
[0022] The mass percentage content of each component in the molten material described in step (2) is as follows: Al: 6%, Zn: 3.5%, Mn: 1.5%, Li: 0.4%, Zr: 0.2%, Mo: 0.4%, Ti: 0.9%, Si: 0.5%, Ca: 0.6%, Ag: 0.1%, Sb: 0.18%, Se: 0.2%, Cr: 0.12%, La: 0.4%, Y: 0.5%, and the balance is Mg.
[0023] Comparative Example 1 The only difference between Comparative Example 1 and Example 3 is that the mass percentage content of Cr is increased to 0.20%, the mass percentage content of La is increased to 0.80%, and the mass percentage content of Y is increased to 0.90%. Other method steps are the same.
[0024] Comparative Example 2 The only difference between Comparative Example 2 and Example 3 is that the addition of La element component in the overall composition is omitted, and the other method steps are the same.
[0025] Comparative Example 3 The only difference between this comparative example 3 and example 3 is that the addition of La and Y elements in the overall composition is omitted, and other method steps are the same.
[0026] Comparative Example 4 The only difference between Comparative Example 4 and Example 3 is that the addition of Cr, La and Y elements in the overall composition is omitted, and other method steps are the same.
[0027] In order to compare the effects of the present invention, the performance tests were conducted on the magnesium-aluminum alloys obtained in the above-mentioned embodiment 3 and comparative embodiments 1-4. The specific comparative data are shown in the following Table 1: Table 1
[0028] Note: The H2 release amount described in Table 1 above is an indicator for evaluating the corrosion resistance of magnesium-aluminum alloys. Specifically, the magnesium-aluminum alloys corresponding to the above groups are immersed in the solutions shown in Table 2 below. After immersion treatment for 180 hours, the total amount of hydrogen generated is measured to characterize the corrosion resistance of magnesium-aluminum alloys.
[0029] Table 2
[0030] It can be seen from Table 2 above that the magnesium-aluminum alloy prepared by the method of the present invention has significant improvements in both corrosion resistance and strength properties. It can be seen that the Cr, La and Y element components have a good synergistic effect, and the amount of addition is not the more the better. The corrosion resistance and strength of the magnesium-aluminum alloy can be controlled by controlling the amount of addition, so as to prepare better materials or products suitable for different use conditions and requirements, which are very competitive in the market and have great value for promotion and application.
Claims
1. A treatment process for improving the surface properties of a pressure gauge spring tube raw material, characterized in that: The steps include: (1) First, pure magnesium, aluminum ingots, and zinc ingots are mixed together, and then put into a furnace for melting. The melting process is carried out by heating at low temperature first and then at high temperature; (2) Adding Mg-Mn master alloy, Mg-Li master alloy, Al-Zr master alloy, Mg-Mo master alloy, Mg-Ti master alloy, Mg-Si master alloy, Mg-Ca master alloy, Mg-Ag master alloy, Al-Mg-Sb master alloy, Al-Mg-Se master alloy, Al-Cr master alloy, Mg-La master alloy and Mg-Y master alloy into the melting furnace of step (1) in sequence; After the co-melting is completed, a molten material is obtained; (3) transferring the molten material obtained in step (2) into a refining furnace, leaving it to stand for 40 to 50 minutes and then casting it into an ingot, and then removing the cold shut and oxide layer on the surface of the ingot to obtain a primary magnesium-aluminum alloy ingot; (4) The primary magnesium-aluminum alloy ingot obtained in step (3) is subjected to solid solution strengthening and aging treatment to obtain a finished magnesium-aluminum alloy.
2. A treatment process for improving the surface properties of a pressure gauge spring tube raw material according to claim 1, characterized in that: During the melting process in step (1), the environment in the furnace is controlled to be an argon environment.
3. A treatment process for improving the surface properties of a pressure gauge spring tube raw material according to claim 1, characterized in that: The method of heating at low temperature first and then at high temperature described in step (1) is to first heat the furnace to 650-700°C, keep the temperature for 25-30 minutes, and then heat the furnace to 800-840°C, and keep the temperature for 20-25 minutes.
4. The process for improving the surface properties of the raw material of the pressure gauge spring tube according to claim 1, characterized in that: The mass percentage content of each component in the molten material described in step (2) is as follows: Al: 6-9%, Zn: 2-3.5%, Mn: 1.5-2.5%, Li: 0.4-0.8%, Zr: 0.2-0.6%, Mo: 0.1-0.4%, Ti: 0.5-0.9%, Si: 0.2-0.5%, Ca: 0.3-0.6%, Ag: 0.1-0.3%, Sb: 0.18-0.30%, Se: 0.2-0.35%, Cr: 0.05-0.12%, La: 0.2-0.4%, Y: 0.3-0.5%, and the balance is Mg.
5. The process for improving the surface properties of the raw material of the pressure gauge spring tube according to claim 4, characterized in that: The mass percentage content of each component in the molten material is as follows: Al: 8%, Zn: 3%, Mn: 2%, Li: 0.6%, Zr: 0.4%, Mo: 0.3%, Ti: 0.8%, Si: 0.4%, Ca: 0.5%, Ag: 0.2%, Sb: 0.25%, Se: 0.3%, Cr: 0.08%, La: 0.3%, Y: 0.4%, and the balance is Mg.
6. A treatment process for improving the surface properties of a pressure gauge spring tube raw material according to claim 1, characterized in that: During the static treatment described in step (3), the refining furnace is controlled to be an argon gas environment.
7. A treatment process for improving the surface properties of a pressure gauge spring tube raw material according to claim 1, characterized in that: The temperature in the refining furnace described in step (3) is controlled to be 660-720°C.